2004
DOI: 10.3141/1872-04
|View full text |Cite
|
Sign up to set email alerts
|

Rail Access Pricing for Suburban Services in Europe

Abstract: Until recently, Europe was dominated by state-owned, vertically integrated railroads. Lately, European Union (EU) policies and relevant legislation have introduced the legal separation between railroad operations and infrastructure management. Thus, the railroad infrastructure management companies have started applying charges (termed access pricing) to railroad companies for using infrastructure. Although European policies and legislation set the basic access pricing principles, they did not provide specific … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…But MNR operated only 14 daily round trips in 2016, which did not suggest a need for electrification. Not surprisingly, an earlier study suggested dual-mode electric/diesel locomotives were more cost-effective than electrification ( 23 ). Furthermore, in 1984 MNR extended electrification on its Harlem Line, which draws some riders from the Danbury Branch’s catchment zone.…”
Section: Insufficient Ridershipmentioning
confidence: 99%
“…But MNR operated only 14 daily round trips in 2016, which did not suggest a need for electrification. Not surprisingly, an earlier study suggested dual-mode electric/diesel locomotives were more cost-effective than electrification ( 23 ). Furthermore, in 1984 MNR extended electrification on its Harlem Line, which draws some riders from the Danbury Branch’s catchment zone.…”
Section: Insufficient Ridershipmentioning
confidence: 99%